A Study on the MAnagement of Health Promoting Behavior among Adolescents Through Adolescent Friendly Centre Services Approach in a Selected Private school - Shanthi, R. (2016)
The current project aimed to investigate the health promoting behavior among adolescents through the adolescent friendly center services introduced in the selected school. This study further wanted to inspect the receptiveness and perception of adolescent friendly services by parents, teachers and adolescents. Through the process of Triangulation the research design was formulated and applied to suit the concept of the study. The information was gathered from 269 adolescents, 160 parents and 21 teachers. The study reported that students were benefitted by the adolescent friendly services. Majority (51.7%) of adolescents perception is that the parent is the suitable person to provide guidance and counseling to them. Parents (76.3%) perceive the Principal/teacher as the best person to provide guidance and counseling to adolescents, while the teachers (71.4%) feel that health care person is the suitable person to provide guidance and counseling to students. A greater number of male (80.19%) and female adolescents (87.34%) reported that education regarding reproductive health and medical checkups were beneficial to them. Guidance and counseling was the most benefitted intervention which was evidenced by a huge number of students self-report that it was beneficial (75.24% in boys and 53.64% of girls). More than half of the boys and girls (55.44% of boys and 51.89%) confronted that the adolescent friendly services created awareness among them. The findings from this study report that specifically there was a comparable difference in scores against one domain (self at P<0.01) of the multi-dimensional student life satisfaction scale before and after attending the adolescent friendly services. Ultimately it was found that Adolescent Friendly Center Services helped students greatly related to identification and management of adolescent health issues, study problems and its management.